E-105 Antibodies against ebola virus: Results of the viral hemorrhagic fever immunotherapeutic consortium. (January 2016) - Dye, John; Chandran, Kartik; Kobinger, Gary; Kawaoka, Yoshihiro; Zeitlin, Larry; Ward, Andrew; Nykiforuk, Cory; Aman, Javad; Lai, Jonathan; Saphire, Erica
Abstract : The Viral Hemorrhagic Fever Immunotherapeutic Consortium is a field- wide, global collaboration that aims to understand which antibodies are effective against filoviruses and arenaviruses and why, and how maximally effective therapeutic cocktails could be assembled. In 2007, it was found that a potent neutralizing mAb was unable to control the course of Ebola virus infection. In 2012, however, it was determined that cocktails of mAbs, including non-neutralizing antibodies, could provide lifesaving postexposure protection against Ebola virus. After these results, the questions in the field were: Is a cocktail of mAbs (vs. a single mAb) necessary? Which combinations offer additive or synergistic functions? Which compete? Which are best? And why? Does in vitro neutralization correlate with in vivo protection? If not, why not? The likely requirement of more than one antibody to mitigate escape, the rarity of the most effective antibodies, and the number of unknowns in terms of the best correlates of protection suggested a large scale, multidisciplinary approach as the best way forward. Over 25 laboratories across 10 countries organized to analyze their assembled pool of mAbs using structural, biochemical, cellular and in vivo analysis. One key facet of this consortium is that all the mAbs are de-identified, for impartial analysis. A second key facet is its scale: antibodies from multiple labs are being compared side-by- side under the same assay condtiions ("apples to apples"), expediting selection, and allowing cocktails to be assembled using rare antbodies from around the globe. The results from the first year will be presented including structures, epitope mapping, and functional analysis. We find that only some potential antibody epitopes consistently lead to in vitro neutralization; others offer protection in the absence of in vitro neutralization.